Japanese postcolonial urbanism: city, landscape and experience in Changchun, Manchuria, 1932-1957 - Xu, Yiming (2024)
This thesis investigates the historical geography of Changchun during the colonial (1931-1945) and post-colonial (1945-1957) periods. The main research contents involve Changchun's urban development, changing political landscapes and urban life. As a regional centre within the Japanese Empire in the 20th century, Changchun has received limited attention in postcolonial geographies. The specificity of Japan as an Asian-led colonialism and the articulation of anti-Western discourses distinguished Changchun from colonial cities in western empires. Changchun's urban development in the postwar socialist period further expressed a successful transformation of a capitalist consumer city into a socialist productive city in a short period of time. Based on archives, official publications, historical maps, and interviews, I focus not only on how the city has changed physically and geographically, but also on the shaping of culture and identity by different governments, which affected residents' perceptions of the city.